Power And Resistance of Characters in the Novel Laut Bercerita by Leila S. Chudori: A Critical Discourse Analysis by Michel Foucault - Sholihatun Munawaroh; Sutardi Sutardi; Hendrik Furqon (CV. Edujavare Publishing, 2026)
Literature is always closely related to everyday life, because humans can act as both subjects and objects in a literary work. This study aims to understand the discourse of power and resistance of characters in the novel Laut Bercerita by Leila S. Chudori using Michel Foucault’s Critical Discourse Analysis (AWK), focusing on Power/Knowledge, Discourse, Disciplinary Power, and Governmentality. The method applied is observation and recording, with techniques including reading, listening, and note-taking. Data analysis involves four stages: data preparation and organization, data reduction, data presentation, and conclusion drawing. The results show that (1) the discourse of power appears through supervision, bodily discipline, and efforts to control certain characters, and (2) the discourse of resistance is expressed not only physically but more frequently through knowledge and discussion, such as conveying truth, building shared understanding, and constructing counter-narratives against power. It can be concluded that Laut Bercerita predominantly presents the discourse of resistance as a response to power practices experienced by characters during the New Order era in Indonesia.